A Normative-Analytical Study of Riba and Its Manifestations in Market Exchange within Islamic Commercial Law - Abdul Chamid; Jamal Abdul Aziz (Journal of Islamic Education and Intellectual Discourse (JIED), 2025)
This article analyzes the normative logic of riba and its manifestations within market exchange from the perspective of Islamic legal theory. Drawing on Qur’anic injunctions, Prophetic traditions, and classical as well as contemporary juristic interpretations, the study distinguishes between the primary conception of riba, rooted in debt-based transactions (riba al-qard), and its derivative forms in commercial exchanges (riba al-buyuʿ), such as riba al-fadhl and riba al-nasī’ah. These classifications reflect the broader legal principles of fairness, equivalence, and transparency that underpin Islamic economic ethics. The research employs a qualitative library-based approach to examine authoritative legal sources and scholarly works, enabling a comprehensive understanding of the doctrinal foundations governing the prohibition of riba. The findings reveal that the prohibition is not merely ritualistic or theological in nature but serves a substantive socio-economic function by preventing exploitation, wealth concentration, and market distortions. In addition, the paper highlights contemporary manifestations of riba, including non-transparent credit sales, late-payment penalties, non-cash gold transactions, and conditional sales that create unjust advantage demonstrating how classical legal categories remain relevant in modern financial practices. The study also engages with alternative views, particularly those proposing a distinction between exploitative usury and mutually agreed interest, as articulated by scholars such as Sjafruddin Prawiranegara. Ultimately, this article argues that the normative logic of riba is fundamentally tied to the preservation of distributive justice and ethical balance in economic relations, underscoring the need for Sharia-compliant contractual models that uphold these principles.